Bridging theory and practice via education: Insights from the erasmus mundus journalism programme - Olivera, Cecilia Arregui (Journalism (London, England), 2025)
The disconnect in how practitioners and scholars talk about what journalism is and does, and what it could be or do, is often striking. With more universities and other institutions worldwide offering journalism education, and the growing number of journalists turned scholars or instructors, there have been sporadic efforts to bridge the pervasive gap between theory and practice. In this paper, I discuss some of the challenges and opportunities of bridging said gap by drawing on the Erasmus Mundus Journalism Programme as a case study. I delve into some ways in which we deal with co-teaching across institutions to train an exceptionally diverse group of students with a global, collaborative, and interdisciplinary mindset. Finally, I claim that we tend to talk about the theory-practice gap in rather narrow terms and point towards ways to rethink the directionality of this relationship to further a truly reflective and critical journalism education.